Kinerja Keuangan Bank Muamalat melalui Pendekatan Islamicity Performance Index - Zahro, Umi Indasyah; Musadad, Ahmad; Mustaniroh, Mustaniroh; Fajar, Fajar; Pujiati , Tri (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
This article evaluates the financial performance of Bank Muamalat Indonesia from 2022 to 2024 based on sharia principles using the Islamicity Performance Index (IPI) developed by Shahul Hameed. The purpose of this study is to measure the extent to which Bank Muamalat applies Islamic principles in its financial operations through six key indicators: Profit Sharing Ratio, Zakat Performance Index, Equitable Distribution Ratio, Director–Employee Welfare Ratio, Islamic Investment vs Non-Islamic Investment, and Islamic Income vs Non-Islamic Income. The study employed a qualitative descriptive method using documentation and literature review. The results indicate that the Profit Sharing Ratio has increased yearly, reflecting a strong commitment to Islamic profit-sharing principles. Conversely, the Zakat Performance Index shows a declining trend, suggesting a need for greater social responsibility. The ratio of income from halal sources remained high and stable, demonstrating compliance with Islamic financial norms. Meanwhile, the Equitable Distribution Ratio and Director–Employee Welfare Ratio fluctuated but remained within acceptable ranges. These findings indicate that, overall, Bank Muamalat's financial performance aligns with sharia compliance, although some areas require improvement. The IPI-based evaluation provides strategic insights for measuring and enhancing the sharia adherence of Islamic financial institutions.